Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Tundra Vegetation Community Type, Not Microclimate, Controls Asynchrony of Above‐ and Below‐Ground Phenology - Elise C. Gallois; Isla H. Myers‐Smith; Colleen M. Iversen; Verity G. Salmon; Laura L. Turner; Ruby An; Sarah C. Elmendorf; Courtney G. Collins; Madelaine J. R. Anderson; Amanda Young; Lisa Pilkinton; Gesche Blume‐Werry; et al. (Global Change Biology, 2025)
The below‐ground growing season often extends beyond the above‐ground growing season in tundra ecosystems and as the climate warms, shifts in growing seasons are expected. However, we do not yet know to what extent, when and where asynchrony in above‐ and below‐ground phenology occurs and whether variation is driven by local vegetation communities or spatial variation in microclimate. Here, we combined above‐ and below‐ground plant phenology metrics to compare the relative timings and magnitudes of leaf and fine‐root growth and senescence across microclimates and plant communities at five sites across the Arctic and alpine tundra biome. We observed asynchronous growth between above‐ and below‐ground plant tissue, with the below‐ground season extending up to 74% (~56 days) beyond the onset of above‐ground leaf senescence. Plant community type, rather than microclimate, was a key factor controlling the timing, productivity, and growth rates of fine roots, with graminoid roots exhibiting a distinct ‘pulse’ of growth later into the growing season than shrub roots. Our findings indicate the potential of vegetation change to influence below‐ground carbon storage as the climate warms and roots remain active in unfrozen soils for longer. Taken together, our findings of increased root growth in soils that remain thawed later into the growing season, in combination with ongoing tundra vegetation change including increased shrub and graminoid abundance, indicate increased below‐ground productivity and altered carbon cycling in the tundra biome.

Why ecologists struggle to predict coexistence from functional traits - Jacob I. Levine; Ruby An; Nathan J.B. Kraft; Stephen W. Pacala; Jonathan M. Levine (Trends in Ecology & Evolution, 2025)

Small herbivores with big impacts: Tundra voles ( Microtus oeconomus ) alter post‐fire ecosystem dynamics - Jess K. Steketee; Adrian V. Rocha; Laura Gough; Kevin L. Griffin; Ian Klupar; Ruby An; Nicole Williamson; Rebecca J. Rowe (Ecology, 2022)
Fire is an important ecological disturbance that can reset ecosystems and initiate changes in plant community composition, ecosystem biogeochemistry, and primary productivity. As herbivores rely on primary producers for food, changes in vegetation may alter plant–herbivore interactions with important—but often unexplored—feedbacks to ecosystems. Here we examined the impact of post‐fire changes in plant community composition and structure on habitat suitability and rodent herbivore activity in response to a large, severe, and unprecedented fire in northern Alaskan tundra. In moist acidic tundra where the fire occurred, tundra voles ( Microtus oeconomus ) are the dominant herbivore and rely on the tussock forming sedge Eriophorum vaginatum for both food and nesting material. Tundra voles were 10 times more abundant at the burned site compared with nearby unburned tundra 7‐12 years after the fire. Fire increased the habitat suitability for voles by increasing plant productivity and biomass, food quality, and cover through both taller vegetation and increased microtopography. As a result of elevated vole abundance, Eriophorum mortality caused by vole herbivory was two orders of magnitude higher than natural mortality and approached the magnitude of the mortality rate resulting directly from the fire. These findings suggest that post‐fire increases in herbivore pressure on Eriophorum could, in turn, disrupt graminoid recovery and enhance shrub encroachment. Tundra state transitions from graminoid to shrub dominated are also evident following other disturbances and fertilization experiments, suggesting that as Arctic temperatures rise, greater available nutrients and increased frequencies of large‐scale disturbances may also alter plant–animal interactions with cascading impacts on plant communities and ecosystem function.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)